Coherent destruction of tunneling in graphene irradiated by elliptically polarized lasers. (15th November 2016) - Gagnon, Denis; Fillion-Gourdeau, François; Dumont, Joey; Lefebvre, Catherine; MacLean, Steve
Abstract: Photo-induced transition probabilities in graphene are studied theoretically from the viewpoint of Floquet theory. Conduction band populations are computed for a strongly, periodically driven graphene sheet under linear, circular, and elliptic polarization. Features of the momentum spectrum of excited quasi-particles can be directly related to the avoided crossing of the Floquet quasi-energy levels. In particular, the impact of the ellipticity and the strength of the laser excitation on the avoided crossing structure—and on the resulting transition probabilities—is studied. It is shown that the ellipticity provides an additional control parameter over the phenomenon of coherent destruction of tunneling in graphene, allowing one to selectively suppress multiphoton resonances.